UJI DAYA TERIMA AGAR-AGAR DADIH SUSU KERBAU - Yusnina Maisyaroh Lubis; Jumirah .; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Dadih Buffalo milk  can be utilized in making of gelatin/jelly . This study aims to determine the acceptability of student in elementary school  towards Dadih buffalo milk’s gelatin. This study was an experimental research conducted using two treatment. Gelatin with addition of 700 gr dadih buffalo milk  and gelatin with addition of 900 gr dadih buffalo milk . Panellists in this research was 24 students in elementary school . Acceptance data test were analyzed by Friedman’s test. This research was conducted at DesaPangkat Kec.Lembah Sorik Marapi Kab.Mandailing Natal in March and April 2016. The results showed that the acceptance of students in elementary school  against the gelatin with addition of  700 gr dadih buffalo milk and addition of 900 gr dadih buffalo milk classified as they like it. However, based on assessment total scores, gelatin with addition of  700 gr  dadih buffalo milk has a high level of scores. In the case of selecting  a snack  foods, the consumers should recomend the gelatin with buffalo milks as an alternative healthy snack foods to fulfill/supply the good energy sufficiency for student in elementary school.  Still required the diversification of another food with addition of buffalo milk as a meal that have a rich nutrients. Keywords: Gelatin, Dadih Buffalo Milk, Acceptance Test.